Articulating resilience in practice: chains of responsibilisation, failure points and political contestation. Issue 1 (2nd January 2017) - Vilcan, Tudorel
Abstract: Resilience has become a fashionable concept in UK policy-making in the last years. Many commentators have interpreted resilience as a neoliberal strategy that seeks to responsibilise individuals in anticipation of the retreat of centralised forms of risk management and protection. However, the haste with which the concept has been adopted also means that little attention has been paid to how resilience works in practice. This article analyses the implementation of a resilience initiative designed to build community resilience to flooding in the UK. It argues that the implementation of the policy is enabled by a long governmental chain of responsibilisation comprising several linkages that are also endangered by potential failure points where political contestations play out. It concludes that looking for what resilience 'does' requires investigating the implementation of specific resilience policies and the degree to which they are successful.